The Effect of Problem-Solving Skills Training on the Frequency of Selective Episiotomy among Midwives - Mina Ghalenovi; Zahra Abedian; Seyed Reza Mazloom; Negar Asghari (Mashhad University of Medical Sciences, 2019)
Background & aim: The decision on whether or not to do episiotomy is ultimately made by midwives. Problem-solving is an essential skill in the workplace situations, which help overcoming unpredictable circumstances without relying on the others. The aim of this study was to investigate the effect of problem-solving skills training on the frequency of selective episiotomy among midwives. Methods: This randomized clinical trial was conducted on 60 midwives with a minimum of 6 months work experience at selected maternity hospitals in Mashhad, Iran in 2012. The participants were assigned into two intervention (N=30) and control (N=30) groups. The intervention included two 4-hour problem-solving skills training sessions. The midwives in the intervention group conducted two primiparous births before and two after the intervention. The control group just conducted four births. Both groups were asked to complete demographic, occupational as well as Baron problem-solving questionnaire before and after the study and their practice was assessed as selective or non-selective episiotomy based on a checklists.Data were analyzed in SPSS software (version 16) using the Chi-square, Wilcoxon and Mann-Whitney U tests.  Results: There was no significant difference between mean scores of the problem-solving skills among midwives in intervention group before and after the intervention (23.2±2.2 vs 23.1±2, P=0.320). It was the same for control group (P=0.537). Also, no significant difference was observed between the two groups regarding selective episiotomy before (P=0.847) and after the intervention (P = 0.582); although, the rate of selective episiotomy in the intervention group was higher before than after intervention (33.3% vs 41.7%). Conclusion: Problem-solving skills training had no effects on the increased number of selective episiotomies. More research studies with larger sample size are recommend.